PENERAPAN NOSQL DATABASE PADA SISTEM INFORMASI PANTI ASUHAN (STUDI KASUS: PANTI ASUHAN AL AKBAR PEKANBARU) - Elsa Sabilah (2023)
The design of a well-structured database is required for the creation of an information system that suits organization needs. Orphanages have an important role in the social welfare of children. Al Akbar Pekanbaru Orphanage has been established since 2009 and currently this place accommodates 72 foster children. The problem that exists at the Al Akbar Orphanage is that the administrative management and provision of information of the institution are still not fully computerized. The purpose of this research is to provide Al Akbar Orphanage the ease in managing the data and information related to the orphanage by designing a database system and a website-based orphanage information system. In the design of this database, a non-relational database type Not Only SQL (NoSQL)is implemented using the Database Lifecycle (DBLC) method and the data will be stored in the Mongodb database. The result of this research is the creation of a database system that can support the process of designing a website-based Al Akbar Pekanbaru Orphanage information system.